High-pressure-resistant low-permeability hydrogen rubber sealing material and preparation method thereof
By introducing modified nano-potassium aluminum silicate and multiple crosslinking systems into ethylene-propylene rubber, high-pressure and low-permeability hydrogen rubber sealing materials were prepared, which solved the problem of insufficient performance of existing materials in high-pressure hydrogen environment, achieved excellent gas barrier performance, good low-temperature rebound and high-temperature aging resistance, and had the feasibility of industrial production.
Patent Information
- Application Number
- CN202411949855.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-14
AI Technical Summary
In high-pressure hydrogen environment, existing rubber materials are difficult to take into account low permeability, wide temperature range, hydrogen embrittlement resistance and burst resistance. In addition, the feasibility of processing and cost is insufficient, and it cannot meet the safe and reliable operation needs of high-pressure hydrogen storage devices.
By introducing silane-modified sheet nanopotassium aluminum silicate into the ethylene-propylene rubber matrix and adopting a multiple crosslinking system to form a network structure with high crosslinking density. Combining the compatibility of ethylene-propylene rubber with moderate vinyl molar fraction and anti-aging agent, a high-pressure and low-permeability hydrogen rubber sealing material is prepared.
It significantly reduces hydrogen permeability, improves seal safety, enhances the mechanical properties and high and low temperature resistance of the material, ensures that the sealing function is maintained throughout the life cycle, and has the feasibility of industrial mass production.
Smart Images

Figure CN119613876A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber processing, and in particular relates to a high-pressure resistant and low-permeability hydrogen rubber sealing material and a preparation method thereof. Background Art
[0002] As the global demand for clean energy becomes increasingly urgent, hydrogen energy has attracted much attention as a secondary energy source that can achieve "zero emissions". In recent years, the high-pressure hydrogen storage technology required for fuel cell vehicles has been continuously upgraded, and the hydrogen storage pressure has gradually increased from the initial 35MPa to 70MPa. Some studies are even exploring the possibility of 82MPa or higher pressure. The rapid increase in high-pressure hydrogen storage pressure has brought new challenges to the safe and reliable operation of related hydrogen storage devices, especially higher requirements for core sealing parts.
[0003] Although traditional rubber materials (such as nitrile rubber, fluororubber or ordinary EPDM rubber, etc.) perform relatively well in general industrial gas or liquid media, it is often difficult to take into account the following performances at the same time in high-pressure hydrogen environments: 1. Low permeability: Hydrogen molecules are very small and have extremely strong permeability. The microstructure of ordinary rubber materials is easily "invaded" by hydrogen molecules under high pressure. Once the permeability is high, hydrogen leakage may occur, leading to safety hazards. How to effectively reduce the diffusion and penetration of high-pressure hydrogen in the material is one of the keys to the reliable application of seals. 2. Wide temperature application range: High-pressure hydrogen storage and hydrogen transmission devices often need to face extreme temperature ranges: in low-temperature environments (such as -40°C or -50°C), conventional rubber materials have a high glass transition temperature, and the material is prone to hardening or microcracks, which leads to seal failure; in high-temperature environments (such as 100°C or even higher), they face problems such as oxidation and thermal aging, which causes the rubber performance to decay. Sealing materials must have both low-temperature toughness and high-temperature stability to ensure that their sealing function is maintained throughout their life cycle. 3. Hydrogen embrittlement and burst resistance: During the high-pressure hydrogen filling and discharging process, the rapid change in pressure will cause hydrogen molecules to enter and exit the rubber matrix, resulting in micro-stress concentration. When the pressure drops suddenly, the hydrogen molecules dissolved in the rubber network escape in large quantities instantly, and it is very easy to form micro-cracks or even bursts inside or on the surface of the material. This phenomenon is often called hydrogen embrittlement or hydrogen-induced bursting. Therefore, the sealing material is required to have sufficient tensile strength, resilience and fatigue resistance to cope with frequent high-pressure cycles and sudden pressure drops. 4. Processing and cost feasibility: With the large-scale development of the hydrogen energy industry, the demand for seals is also increasing. In addition to meeting high-performance requirements, the material also needs to have the characteristics of industrialized mass production and simple processing technology, while maintaining a relatively reasonable cost. If the sealing material is too expensive or the manufacturing process is too complicated, it will not be conducive to its large-scale promotion in the market.
[0004] Therefore, there is an urgent need to develop a low-permeability hydrogen rubber sealing material that can be stably used in the pressure range of 70MPa and higher, and has excellent comprehensive mechanical properties and high and low temperature adaptability to meet the needs of the rapid development of the hydrogen energy industry in the future. Summary of the invention
[0005] The present invention provides a high-pressure resistant and low-permeability hydrogen rubber sealing material and a preparation method thereof. The material can achieve excellent gas barrier performance under a high-pressure hydrogen environment and has both good low-temperature resilience and high-temperature aging resistance.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows:
[0007] In a first aspect, the present invention provides a high-pressure resistant and low-permeability hydrogen rubber sealing material, comprising the following components in parts by weight:
[0008] 100 parts of ethylene propylene rubber;
[0009] 4-8 parts of active agent;
[0010] 1-3 parts of antioxidant;
[0011] 20-50 parts of nanomaterials;
[0012] Filling reinforcing agent 50-60 parts;
[0013] 2-5 parts of coupling agent;
[0014] Curing agent dicumyl peroxide 3-4 parts;
[0015] 1-2 parts of the vulcanizing agent trienyl triisourate;
[0016] 3-8 parts of vulcanized resin.
[0017] Furthermore, the molar fraction of vinyl in the EPDM rubber is 44%-50%.
[0018] Furthermore, the active agent is 3-5 parts of zinc oxide and 1-3 parts of stearic acid.
[0019] Furthermore, the antioxidant is 4,4′-bis(α,α′-dimethylbenzyl)diphenylamine.
[0020] Furthermore, the filler and reinforcing agent is one or more combinations of white carbon black, N330, and N774.
[0021] Furthermore, the nano material is nano potassium aluminum silicate; the potassium aluminum silicate is subjected to one-dimensional nano-ultrafine treatment and airflow screening, and then subjected to a mixed modification treatment of one or more of vinyl triethoxysilane A-151, vinyl tri(2-methoxyethoxy)silane A-172, and γ-methacryloxypropyltrimethoxysilane A-174 to obtain nano potassium aluminum silicate with a full lamellar structure.
[0022] Furthermore, the coupling agent is one or more combinations of silane coupling agents KH550, KH560, and KH570.
[0023] Furthermore, the cross-linking agent is selected from dicumyl peroxide and the auxiliary cross-linking agent trienyl triisourate and vulcanized resin.
[0024] Furthermore, the nano-potassium aluminum silicate is further compounded with silicon oxide or aluminum oxide to form a heterogeneous nano-sheet layer, and is subjected to double silane modification or plasma surface treatment.
[0025] In a second aspect, the present invention provides a method for preparing a high-pressure resistant and low-permeability hydrogen rubber sealing material, characterized in that it comprises the following steps:
[0026] Take EPDM rubber and nanomaterials and mix them until they are evenly dispersed;
[0027] Add the activator, antioxidant, filler and reinforcing agent and continue mixing;
[0028] After adding dicumyl peroxide, tris(vinyl) triisourate and vulcanized resin, mixing and kneading are performed uniformly to obtain a mixed rubber material. The roller temperature in the above mixing process is not higher than 50° C.;
[0029] Allow the mixed rubber to stand naturally at room temperature for more than 24 hours;
[0030] Pressing the parked rubber material into semi-finished rubber sheets;
[0031] Under the conditions of 160°C-170°C and 11MPa-15MPa, hot press vulcanization is performed for 20min-25min to obtain a hot press vulcanized molded product;
[0032] The hot press vulcanized product is placed at room temperature for more than 16 hours.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention introduces silane-modified flaky nano-potassium aluminum silicate into the ethylene-propylene rubber (EPDM) matrix and utilizes its "brick wall" microscopic barrier structure to achieve the bending transmission of hydrogen molecules in the rubber network, greatly extending the diffusion path, thereby significantly reducing the hydrogen permeability. Test results show that under a working environment with a hydrogen pressure of 70MPa, the permeability coefficient of the material of the present invention can be reduced by about 30%-50% compared with ordinary EPDM, effectively improving the sealing safety.
[0035] Under high pressure, traditional rubber materials are prone to microcracks or bursts. The present invention uses dicumyl peroxide combined with a multiple cross-linking system such as tris-vinyl triisourate and vulcanized resin to form a network structure with a high cross-linking density, which significantly enhances the mechanical properties of the rubber. In the room temperature tensile strength test, the molded product can reach 16-20MPa; it can still maintain a high elasticity and rebound rate at -40°C; and no obvious cracks or bursts occur in the 70MPa rapid hydrogen charging and discharging cycle test.
[0036] In order to take into account the application requirements of a wide temperature range, the present invention uses EPDM with a vinyl molar fraction content of 44%-50%, so that it still has good low-temperature toughness and resilience at -40°C, and through the addition of antioxidant 4,4′-bis(α,α′-dimethylbenzyl)diphenylamine, the material's antioxidant and heat aging resistance in high temperature environments are effectively improved. The corresponding compression permanent deformation test results show that under 90°C×24h conditions, the compression permanent deformation rate of the rubber of the present invention is only 17%-25%, and under 150°C×72h conditions, it can also be maintained in the range of 45%-50%, showing good stability.
[0037] In terms of production technology, the EPDM, nano-potassium aluminum silicate and conventional vulcanizing agents used in the method of the present invention can all be obtained through existing industrialization routes, and the mixing and vulcanization processes are similar to those of conventional rubber products, and the processing equipment investment cost is low, which can ensure large-scale continuous production while maintaining controllable overall costs. Various process and production data show that the preparation process of the material of the present invention has the characteristics of high maturity, high efficiency and easy promotion.
[0038] Of course, the implementation of the various technical solutions of the present invention does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, drawings of other embodiments can be obtained based on these drawings without paying creative work.
[0040] Figure 1 This is a photo of the present invention before the hydrogen permeation resistance test;
[0041] Figure 2 This is a photo of the invention after the hydrogen permeation resistance test. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below by specific embodiments in conjunction with the accompanying drawings. Wherein similar elements in different embodiments adopt associated similar element numbers. In the following embodiments, many detailed descriptions are for making the present application better understood. However, those skilled in the art can easily recognize that some features can be omitted in different situations, or can be replaced by other elements, materials, methods. In some cases, some operations related to the present application are not shown or described in the specification, this is to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations according to the description in the specification and the general technical knowledge in the art.
[0043] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and are not meant to be a required sequence, unless otherwise specified that a certain sequence must be followed.
[0044] The serial numbers of the components in this document, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning. The "connection" and "coupling" mentioned in this application, unless otherwise specified, include direct and indirect connections (couplings).
[0045] Embodiment 1:
[0046] This embodiment provides a high-pressure resistant and low-permeability hydrogen rubber sealing material. The formula components of the sealing material are as follows, in parts by weight:
[0047] 100 parts of ethylene propylene rubber (EPDM);
[0048] 6 parts of active agent; in this embodiment, the active agent is a combination of zinc oxide and stearic acid, wherein zinc oxide is 4 parts and stearic acid is 2 parts.
[0049] 2 parts of antioxidant; in this embodiment, the antioxidant is 4,4′-bis(α,α′-dimethylbenzyl)diphenylamine.
[0050] 30 parts of nanomaterials; the nanomaterial is nano potassium aluminum silicate, which is prepared by one-dimensional nano-ultrafine treatment of potassium aluminum silicate, airflow screening, and then mixed and modified with vinyl triethoxy silane A-151, vinyl tri (2-methoxyethoxy) silane A-172, and γ-methacryloxypropyl trimethoxy silane A-174 to finally form a full-sheet structure.
[0051] 60 parts of the filling reinforcing agent. In this embodiment, the filling reinforcing agent is a combination of N330 and white carbon black, wherein N330 is 40 parts and white carbon black is 20 parts.
[0052] 3 parts of coupling agent; in this embodiment, the coupling agent is KH560.
[0053] Curing agent: 4 parts of diisopropylbenzene peroxide.
[0054] 1 part of vulcanizing agent trienyl triisourate.
[0055] 3 parts of vulcanized resin.
[0056] According to the above-mentioned ratio scheme, this embodiment provides a method for preparing a high-pressure resistant and low-permeability hydrogen rubber sealing material, comprising the following steps:
[0057] Step S1, premixing ethylene propylene rubber (EPDM) and nano-potassium aluminum silicate on an open mill (controlling the roller temperature not higher than 50° C.) for about 5 to 10 minutes to make the nano-materials preliminarily and evenly dispersed in the rubber matrix.
[0058] Step S2: Add zinc oxide, stearic acid, antioxidant, filler and reinforcing agent and silane coupling agent KH560 in sequence, and continue to mix until uniformly dispersed. During this process, keep a low temperature to avoid premature crosslinking.
[0059] Step S3: Finally, add dicumyl peroxide, tris(vinyl) triisourate and vulcanized resin, and continue mixing for several minutes to ensure that each component is fully dispersed in the rubber material to obtain a mixed rubber material.
[0060] Step S4, placing the obtained mixed rubber material at room temperature and leaving it naturally for more than 24 hours to release the internal stress and further interact with the additives and rubber molecules to improve the subsequent vulcanization effect.
[0061] Step S5, hot-pressing and vulcanizing the mixed rubber material for 20 minutes at a temperature of 160° C. and a pressure of 15 MPa; through this process, the crosslinking agent and the co-vulcanizing agent fully react to form a high-density three-dimensional crosslinked network.
[0062] Step S6, after taking out the rubber product formed by hot pressing and vulcanization, leaving it to stand at room temperature for more than 16 hours to further stabilize the arrangement of the molecular segments, reduce the internal stress and ensure the stability of the physical properties; finally, a high-pressure resistant and low-permeability hydrogen rubber sealing material is obtained.
[0063] The performance test of the above-mentioned high pressure resistant and low permeability hydrogen rubber sealing material was carried out, and the results are as follows:
[0064] The hydrogen permeability coefficient of the high-pressure, low-permeability hydrogen rubber sealing material of this embodiment is significantly lower than that of conventional ethylene-propylene rubber (EPDM) material; the tensile strength can reach 17 to 18 MPa, and the elongation at break is 120%; it still has good elasticity at -48 to -52°C; and it exhibits a lower deformation rate at both high temperature (90°C×24h) and low temperature (-40°C).
[0065] Embodiment 2:
[0066] The high-pressure and low-permeability hydrogen rubber sealing material provided in this embodiment has the following formula components in parts by weight:
[0067] 100 parts of ethylene propylene rubber (EPDM).
[0068] 8 parts of active agent; including 5 parts of zinc oxide and 3 parts of stearic acid.
[0069] 3 parts of antioxidant; 4,4′-bis(α,α′-dimethylbenzyl)diphenylamine is selected.
[0070] 50 parts of nanomaterials; nano potassium aluminum silicate is selected, which is prepared by subjecting potassium aluminum silicate to one-dimensional nano-ultrafine treatment, airflow screening, and then mixed modification treatment with vinyl triethoxy silane A-151, vinyl tri (2-methoxyethoxy) silane A-172, and γ-methacryloxypropyl trimethoxy silane A-174 to finally form nano potassium aluminum silicate with a full sheet structure; in order to further enhance the barrier and mechanical properties of the material, in this embodiment, the nano potassium aluminum silicate is further compounded with silicon oxide to form a heterogeneous nano sheet layer, and subjected to a double silane-modified surface treatment.
[0071] 50 parts of filler and reinforcing agent; 30 parts of N330 and 20 parts of white carbon black.
[0072] 5 parts of coupling agent; KH560 is selected.
[0073] 3 parts of vulcanizing agent; dicumyl peroxide is selected.
[0074] 2 parts of vulcanizing agent: trienyl triisourate is selected.
[0075] 8 parts of vulcanized resin.
[0076] In this embodiment, 50 parts of nano-potassium aluminum silicate is selected, and firstly subjected to one-dimensional nano-ultrafine treatment and airflow screening to obtain a flaky powder with a relatively uniform particle size distribution; on this basis, a mixed modification of multiple silane coupling agents (including A-151, A-172, and A-174) is introduced into its surface, so that the silane groups are firmly bonded around the potassium aluminum silicate flakes to form a stable organic-inorganic bonding interface.
[0077] After the initial modification, this embodiment further compounds nano-potassium aluminum silicate with silicon oxide (SiO2) nanopowder in order to construct a heterogeneous nano-sheet structure at the microscopic level. To this end, through precise proportioning and secondary grinding and dispersion, a small amount of silicon oxide powder is stably attached to the side or surface of the potassium aluminum silicate sheet; this heterogeneous sheet can simultaneously possess the high diameter-to-thickness ratio of potassium aluminum silicate and the high rigidity characteristics of silicon oxide, which improves the mechanical properties of the material while also enhancing the barrier capacity.
[0078] In order to further reduce the aggregation of the composite sheet in the rubber matrix and improve its interfacial compatibility with the matrix, the composite sheet material was modified again by double silane coupling treatment; by adjusting the silane type and treatment conditions, active functional groups were introduced on the surface of silicon oxide to form a multi-point cross-linking structure with the modified potassium aluminum silicate. Compared with single modification, this double modification significantly enhances the dispersion stability of the sheet and makes the sheet present a more regular and compact layer-by-layer stacking in the EPDM network.
[0079] In summary, this embodiment finally obtains heterogeneous nano-potassium aluminum silicate with a full-sheet structure through multiple steps such as refined one-dimensional ultrafine processing, airflow classification screening, multi-silane coupling modification, and composite processing with silicon oxide. This nanomaterial not only effectively constructs a "brick wall" or "maze" barrier channel, thereby greatly reducing the hydrogen permeability, but also provides a higher mechanical reinforcement effect for the rubber matrix; combined with the optimized formula of other components in this embodiment (such as vulcanizing agent, activator, antioxidant, etc.), it can maintain excellent sealing reliability and stability in a high-pressure hydrogen environment.
[0080] This embodiment provides a method for preparing a high-pressure resistant and low-permeability hydrogen rubber sealing material, which is the same as that of Embodiment 1.
[0081] The performance test of the above-mentioned high pressure resistant and low permeability hydrogen rubber sealing material is carried out. The test process is shown in Figure 1 and Figure 2 , the results are as follows:
[0082] The hydrogen permeability coefficient is further reduced compared with Example 1; due to the increase in the content of the vulcanized resin, the hardness is slightly increased compared with Example 1, and the tensile strength is about 18-19 MPa; good resilience is still maintained at low temperatures (-40°C).
[0083] Embodiment 3:
[0084] The high-pressure and low-permeability hydrogen rubber sealing material provided in this embodiment has the following formula components in parts by weight:
[0085] 100 parts of ethylene propylene rubber (EPDM).
[0086] 4 parts of active agent; including 3 parts of zinc oxide and 1 part of stearic acid.
[0087] 1 part of antioxidant; 4,4′-bis(α,α′-dimethylbenzyl)diphenylamine is selected.
[0088] 20 parts of nanomaterials; nano potassium aluminum silicate is selected and modified by vinyl triethoxysilane A-151 to finally form a full-flaky structure. After the modification, it becomes a full-flaky structure.
[0089] 60 parts of filler and reinforcing agent; 40 parts of N330 and 20 parts of white carbon black.
[0090] 2 parts of coupling agent; KH560 is selected.
[0091] 4 parts of vulcanizing agent; dicumyl peroxide is selected.
[0092] 1 part of vulcanizing agent; trienyl triisourate is selected.
[0093] 3 parts of vulcanized resin.
[0094] This embodiment provides a method for preparing a high-pressure resistant and low-permeability hydrogen rubber sealing material. The specific preparation process of this embodiment is similar to that of Embodiments 1 and 2, including:
[0095] S1. Pre-mix on an open mill (EPDM and nanomaterials, roller temperature ≤ 50°C);
[0096] S2, gradually add active agent, antioxidant, filling reinforcing agent and coupling agent, and mix evenly;
[0097] S3, finally adding a crosslinking agent and a vulcanizing agent to obtain a mixed rubber material;
[0098] S4, park for 24 hours;
[0099] S5, hot press vulcanization at 160°C and 15MPa for 20 minutes;
[0100] S6. Place at room temperature for more than 16 hours to obtain the final product.
[0101] The performance test of the above-mentioned high pressure resistant and low permeability hydrogen rubber sealing material was carried out, and the results are as follows:
[0102] Hydrogen permeability: Compared with Examples 1 and 2, the amount of nanomaterials used is relatively reduced, but it still has a barrier effect that is significantly better than that of ordinary EPDM, and the permeability coefficient is at a relatively low level, which can meet the general needs of medium and high pressure hydrogen environments.
[0103] Mechanical properties: tensile strength is about 16MPa, elongation at break is maintained at 100% to 120%, and still has good elasticity at -40°C. The relatively reduced content of active agent and nanomaterial makes the hardness of the rubber slightly lower than that of Example 2, but still meets the basic requirements of high-pressure sealing.
[0104] High and low temperature resistance and cross-linking degree: The adaptability of this embodiment to high and low temperatures is still excellent, especially no brittle cracking occurs at -40°C, and the compression permanent deformation is also maintained within the qualified range under high temperature environments of 90°C×24h or 150°C×72h, indicating that its cross-linked network structure is stable and the aging rate is low.
[0105] Table 1 below shows the test results of physical properties of sealing materials of multiple groups of embodiments of the present invention.
[0106]
[0107] Table 1
[0108] Table 1 below shows the hydrogen permeation resistance test results of multiple groups of embodiments of the present invention.
[0109]
[0110] Table 2
[0111] The low permeability mechanism of this embodiment is as follows: the nano-potassium aluminum silicate of this embodiment, after being modified by a silane coupling agent, presents a sheet-like "layer-by-layer stacking" structure in ethylene-propylene rubber (EPDM), as if constructing a "maze-like" barrier channel, greatly extending the diffusion path of hydrogen molecules and significantly reducing the hydrogen permeation rate.
[0112] Ethylene propylene rubber (EPDM) itself has a relatively stable molecular skeleton under high temperature, low temperature and high pressure environments. Combined with the synergistic enhancement of the nanosheet layer, it can effectively inhibit the penetration of hydrogen molecules.
[0113] The high-pressure anti-burst principle of this embodiment is as follows: After this embodiment adopts a peroxide vulcanization system (diisopropylbenzene peroxide) and vulcanizing agents such as triolefin triisourate and vulcanizing resin, a more uniform and dense cross-linking network can be formed inside the rubber matrix.
[0114] When the hydrogen pressure changes rapidly, the microcracks inside the material are not easy to expand, so it has higher anti-burst performance.
[0115] The high and low temperature resistance and mechanical properties of this embodiment are analyzed as follows: This embodiment uses ethylene-propylene rubber (EPDM) with a moderate vinyl mole fraction, combined with activators such as zinc oxide and stearic acid and an antioxidant 4,4′-bis(α,α′-dimethylbenzyl)diphenylamine, which can maintain low-temperature flexibility at -40°C and maintain stable strength and resilience in the temperature range above 100°C.
[0116] This comprehensive property makes the material widely applicable to hydrogen sealing components in harsh environments of high cold or high temperature.
[0117] The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not intended to limit the present invention. For those skilled in the art, according to the concept of the present invention, some simple deductions, modifications or substitutions can be made.
Claims
1. A high pressure resistant and low permeability hydrogen rubber sealing material, characterized in that: By weight, it includes the following components: 100 parts of ethylene propylene rubber; 4-8 parts of active agent; 1-3 parts of antioxidant; 20-50 parts of nanomaterials; Filling reinforcing agent 50-60 parts; 2-5 parts of coupling agent; Curing agent dicumyl peroxide 3-4 parts; 1-2 parts of the vulcanizing agent trienyl triisourate; 3-8 parts of vulcanized resin.
2. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 1, characterized in that: The molar fraction of vinyl in the EPDM rubber is 44%-50%.
3. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 1, characterized in that: The active agent is 3-5 parts of zinc oxide and 1-3 parts of stearic acid.
4. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 1, characterized in that: The antioxidant is 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine.
5. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 1, characterized in that: The filler and reinforcing agent is one or more combinations of white carbon black, N330, and N774.
6. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 1, characterized in that: The nano material is nano potassium aluminum silicate; the potassium aluminum silicate is subjected to one-dimensional nano-ultrafine treatment, airflow screening, and then mixed and modified with one or more of vinyl triethoxysilane A-151, vinyl tri(2-methoxyethoxy)silane A-172, and γ-methacryloxypropyltrimethoxysilane A-174 to obtain nano potassium aluminum silicate with a full-sheet structure.
7. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 1, characterized in that: The coupling agent is one or more combinations of silane coupling agents KH550, KH560, and KH570.
8. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 1, characterized in that: The cross-linking agent is dicumyl peroxide and auxiliary cross-linking agents trienyl triisourate and vulcanized resin.
9. The high pressure resistant and low permeability hydrogen rubber sealing material according to claim 6, characterized in that: The nano-potassium aluminum silicate is further compounded with silicon oxide or aluminum oxide to form a heterogeneous nano-sheet layer, and is subjected to double silane modification or plasma surface treatment.
10. A method for preparing a high-pressure resistant and low-permeability hydrogen rubber sealing material, characterized in that: The steps include: Take EPDM rubber and nanomaterials and mix them until they are evenly dispersed; Add the activator, antioxidant, filler and reinforcing agent and continue mixing; After adding dicumyl peroxide, tris(vinyl) triisourate and vulcanized resin, mixing and kneading are performed uniformly to obtain a mixed rubber material. The roller temperature in the above mixing process is not higher than 50°C. Allow the mixed rubber to stand naturally at room temperature for more than 24 hours; Pressing the parked rubber material into semi-finished rubber sheets; Under the conditions of 160°C-170°C and 11MPa-15MPa, hot press vulcanization is performed for 20min-25min to obtain a hot press vulcanized molded product; The hot press vulcanized product is placed at room temperature for more than 16 hours.
Citation Information
Patent Citations
Ethylene / Alpha-olefin copolymer rubber composition
JP1996208913A
Cited By
Ethylene-propylene-diene monomer rubber material for sealing fuel cell and preparation method of ethylene-propylene-diene monomer rubber material
CN122404860A